2020
DOI: 10.1128/mbio.01073-20
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli K-12 Lacks a High-Affinity Assimilatory Cysteine Importer

Abstract: The most direct route by which microbes might assimilate sulfur would be by importing cysteine. However, alone among the amino acids, cysteine does not have well-characterized importers. We determined that Escherichia coli can rapidly import cysteine, but in our experiments, it did so primarily through the LIV ATP-driven system that is dedicated to branched-chain amino acids. The affinity of this system for cysteine is far lower than for Leu, Ile, and Val, and so in their presence, cysteine is excluded. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…We hypothesized that L. iners ’s restricted ability to use exogenous Cys sources might reflect a limited repertoire of transport mechanisms for Cys and Cys-containing molecules in comparison to other lactobacilli. Cys transporters are not well-characterized in bacteria compared to transporters for other amino acids 47 . Uptake of Cys and Cys-containing molecules is described as occurring through multiple known or putative mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We hypothesized that L. iners ’s restricted ability to use exogenous Cys sources might reflect a limited repertoire of transport mechanisms for Cys and Cys-containing molecules in comparison to other lactobacilli. Cys transporters are not well-characterized in bacteria compared to transporters for other amino acids 47 . Uptake of Cys and Cys-containing molecules is described as occurring through multiple known or putative mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of Cys and Cys-containing molecules is described as occurring through multiple known or putative mechanisms. These include the well-characterized cystine transport systems TcyABC, TcyJKLMN, and TcyP 48 , a putative Cys ABC transporter associated with the Cys-binding protein CjaA 47, 49 , and the heterodimeric ABC transporter CydDC encoded by the redox-regulating locus cydABCD 50 , a conserved system that exports both Cys and GSH to the periplasm in E. coli 50 and is proposed to perform glutathione uptake in lactobacilli 51 . Analysis of our expanded Lactobacillus genome catalogs annotated using eggNOG revealed that genomes of all non- iners species encoded cydABCD , while L. crispatus , L. vaginalis , and some L. gasseri encoded one or more predicted cjaA orthologs and L. jensenii , L. gasseri , and L. vaginalis each encoded one or more cystine transport systems (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations